The peripheral sensitivity profile at the saccade target reshapes during saccade preparation. (June 2021) - Kroell, Lisa M.; Rolfs, Martin
Abstract: Goal-directed eye movements (saccades) bring peripheral objects of interest into high-acuity foveal vision. In preparation for the incoming foveal image, the perception of the saccade target may sharpen gradually before the eye movement is executed. Indeed, previous studies suggest that pre-saccadic attention shifts enhance sensitivity to high spatial frequencies (SFs) more than sensitivity to lower SFs. This pattern, however, was observed within a narrow frequency range and may reflect local changes in the shape of a broader underlying sensitivity profile. Depending on the development of the profile's shape, SFs above the previously examined range may profit less from saccade preparation. To assess the impact of saccade preparation on the shape of a broader sensitivity profile, we prompted observers to discriminate the orientation of a sinusoidal grating (the probe) presented briefly at the target of an impending saccade, at 10 dva (degree of visual angle) eccentricity. The probe's SF ranged from 1 to 5.5 cycles per dva (cpd) and was unpredictable on a given trial. We fitted observers' response accuracies across SFs with a log-parabolic, that is, inverted U-shaped function. Long before saccade onset, the profile peaked at .6 cpd and dropped off towards lower and higher SFs with broad bandwidth. During saccade preparation, the peak of the profile increased and shifted towards higher SFs while the bandwidth of the profile decreased. As a consequence of this reshaping process, pre-saccadic enhancement increased with SF up to 2.5 cpd, corroborating previous findings. Sensitivities to higher SFs, however, profited less from saccade preparation. We conclude that the extent of pre-saccadic enhancement to a particular SF is governed by its position on a broader sensitivity profile which reshapes substantially during saccade preparation. The shift of the profile's peak towards higher SFs increases resolution at the saccade target even when the features of relevant visual information are unpredictable. Graphical abstract: Image 1